2018
DOI: 10.1186/s40066-018-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey of mushroom consumption and the possible use of gamma irradiation for sterilization of compost for its cultivation in Southern Ghana

Abstract: Background: Mushroom cultivation is increasingly becoming a serious agribusiness in Ghana, especially at the time when entrepreneurship is being encouraged to reduce the pressure of employment in the government sector and also due to its nutritional and medicinal attributes.Methods: A survey was carried out using the rapid appraisal method to review the existing methods of sterilization, use of gamma radiation in substrate sterilization and food preservation, preference of mushrooms in Ghana by consumers and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Due to benefits derived from mushroom production, many indigenous and commercial cultivation methods have been developed and put in place to domesticate mushrooms [18]. Cultivation of oyster mushroom on tree stumps and wood logs was initiated on an experimental basis in Germany by a scientist called Flack in the year 1917. e growing technology was later perfected in the USA by Block, Tsao, and Hau [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to benefits derived from mushroom production, many indigenous and commercial cultivation methods have been developed and put in place to domesticate mushrooms [18]. Cultivation of oyster mushroom on tree stumps and wood logs was initiated on an experimental basis in Germany by a scientist called Flack in the year 1917. e growing technology was later perfected in the USA by Block, Tsao, and Hau [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation of oyster mushroom on tree stumps and wood logs was initiated on an experimental basis in Germany by a scientist called Flack in the year 1917. e growing technology was later perfected in the USA by Block, Tsao, and Hau [19]. Cultivation of mushrooms has become a very profitable commercial agribusiness in most developing and developed countries such as the USA, Great Britain, China, Asia, Japan, Europe South Africa, and Ghana with China as the biggest producer producing about 3,918,300 tons each year [18]. China produces more than 85% of all oyster mushrooms worldwide; however, 95% of the total China production is for domestic consumption [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The findings also showed that the consumers frequently consumed the white button mushroom compared to the other types of mushrooms. Contrary to their findings, a survey conducted by Kortei et al (2018) on mushroom consumption and the possible use of gamma Keywords: edible mushrooms, gender, preferences, choice experiment, mixed logit (JEL Classification: B21, D12) irradiation for sterilization of compost for its cultivation in Southern Ghana revealed that 72% of consumers preferred oyster mushroom to the termite and straw mushrooms.…”
Section: Introductionmentioning
confidence: 77%
“…Consumption preference considering some mushroom species depends on the evaluated public and country, since the studies which were carried out in India reported that white bud (Agaricus bisporus) is the most consumed macrofungus (Shirur et al, 2014), whereas the oyster mushroom (Pleurotus spp.) is the most popular in Ghana (Kortei et al, 2018).…”
Section: Market Survey Of Mushroom Consumersmentioning
confidence: 99%